PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN MANAJEMEN LABA TERHADAP KINERJA KEUANGAN - Anthony Holly; Lukman Lukman (Magister Akuntansi, Universitas Atma Jaya Makassar, 2021)
This research is aimed to investigate the impact of managerial ownership, institutional ownership and earning management to financial performance. This research using companies listed in Indonesia Stock Exchange (IDX) as sample in 2016-2018. Sample selected by purposive sampling method. Data type used in this study is quantitative data and analyzed using multiple linear regression analysis to analysis dependent variable, financial performance, and independent variable,managerial ownership, institutional ownership and earning management.The result of the research revealed managerial ownership and earning management has no significant effect on financial performance, but Institutional ownership has positiveandsignificant effect on financial performance